FINANCIAL LITERACY AND FINANCIAL RESOURCES RETIREMENT - Lestari, Emi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study is to analyze and synthesize a theory that explains the relationship between financial literacy and pensioners' financial resources in the sandwich generation. This study uses a qualitative approach with the literature review method, which is an approach that examines and synthesizes previous research by selecting relevant literature, analyzing and solving and interpreting the synthesis of literature. This study examines 43 articles sourced from the Google Scholar database, Mandeley Search, Emerald Insight and Harzing's Publish or Pherish. This study presents the theoretical basis, other explanatory variables and research results from previous literature. Theories that underlie it include life cycle theory, expected utility theory, and planned behavior theory. The synthesis of the research results shows that good and reliable financial literacy has a close relationship with retirement financial resources. This research contribution provides important knowledge and effective strategies for increasing financial resources during retirement.